PENGARUH HEDONIC MOTIVATION TERHADAP SOCIAL MEDIA PRODUCT BROWSING DAN DAMPAKNYA TERHADAP PURCHASE INTENTION PADA MAHASISWA UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Risang Bagus Hastungkara Aji; Henny Welsa; Ignatius Soni Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is to analyze and explain the effect of Hedonic motivation on social media product browsing and its impact on purchase intentions at Sarjanawiyata Tamansiswa University students in Yogyakarta. The sample used in this study is customers who buy and use social media. Accidental sampling is used as a sampling technique. Researchers used a questionnaire to collect primary data with a total of 213 respondents. In this research researchers used regression analysis to determine the effect of hedonic motivation on the search for social media products and their impact on purchase intentions. The results show that hedonic motivation has a positive effect on social media product browsing. Hedonic motivation and social media product browsing were found to partially influence purchase intention. Furthermore, social media product browsing mediates the effect of hedonic motivation on purchase intention.Keywords: Hedonic motivation, social media product browsing, purchase intention